2019
DOI: 10.1680/jgeot.17.p.133
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual constitutive model unifying slurried (saturated), compacted (unsaturated) and dry states

Abstract: Reconstituted and compacted soils are commonly assumed to exhibit a fundamentally different behaviour due to different microstructure. However, inspection of pore size distribution of the same soil in compacted and reconstituted states suggests that the boundary between these two states is more blurred. This paper explores the continuity between the microstructure of reconstituted and compacted states of kaolin clay and formulates a conceptual constitutive model unifying these states. Clay samples were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…The straightforward conclusion drawn by Pedrotti and Tarantino (2018) is that, in compacted samples, macro-pores are filled with air and micro-pores are filled with water (Figure 2b). Accordingly, the microstructure of a compacted sample can be assumed to be the 'sum' of the PSDs of the wet (saturated) and dry part as shown in Figure 3.…”
Section: The Microstructural Model For Compacted Claysmentioning
confidence: 90%
See 4 more Smart Citations
“…The straightforward conclusion drawn by Pedrotti and Tarantino (2018) is that, in compacted samples, macro-pores are filled with air and micro-pores are filled with water (Figure 2b). Accordingly, the microstructure of a compacted sample can be assumed to be the 'sum' of the PSDs of the wet (saturated) and dry part as shown in Figure 3.…”
Section: The Microstructural Model For Compacted Claysmentioning
confidence: 90%
“…Tarantino and De Col (2008) observed that the characteristic pore size associated with micro-and macro-porosities in compacted kaolin remain the same from very low water Submitted to Geomechanics for Energy and Environment 6 contents (dry-side of optimum) up to the water content at optimum. Pedrotti and Tarantino (2018) carried out an experimental investigation to explore the microstructure of compacted kaolin clay and its interplay with the microstructure of clays reconstituted from slurry and compressed from dry powder. They showed that the PSD of kaolin reconstituted from slurry (formed water-saturated) and kaolin compressed from dry powder (formed air-saturated) overlap astonishingly with the modal sizes associated with the micro-and macro-pores of the compacted samples (Figure 2a).…”
Section: The Microstructural Model For Compacted Claysmentioning
confidence: 99%
See 3 more Smart Citations